Design and Synthesis of E7820/Tasisulam Hybrids as Potential DCAF15 Binders - Sofiane Hocine; Victor Cosson; Remi Calandrino; Timea Baló; Jayson Alves Bordelo; Sébastien Triboulet; Laure Caruana; Laurence Klipfel; Sandrine Calis; András Herner; Stephen Hanessian (Reactions, 2025)
We describe the design and synthesis of a series of N-[arylsulfonyl]-1H-pyrrole-2-carboxamides as hybrid analogs of the DCAF15 binders E7820 and tasisulam, two representative SPLAMs (sulfonamide-containing molecular glues). These hybrid molecules were designed to combine the key interactions of both parent ligands within the DCAF15 binding site, as supported by docking studies. Binding affinity was evaluated using fluorescence polarization assays, and structure–activity relationships were established, highlighting the importance of dichlorinated pyrrole moieties. Selected compounds were also tested in HCT116 cells to assess in vitro activity.